ANALYSIS OF PRODUCTION COSTS OF BROILER CHICKENS GIVEN MORINGA OLEIFERA LEAF FLOUR SUBSTITUTION - Nanda Noviana; Mulyadi; Dedhi Yustendi; Zulkifli (Jurnal Penelitian Progresif, 2026)
Broiler chickens are a poultry commodity that has promising business prospects due to their short rearing time, rapid growth, and high demand for meat. However, high feed costs, which reach 60–70% of total production costs, are a major obstacle in this business. One alternative to reduce feed costs is to utilize local feed ingredients with high nutritional value, such as moringa leaf flour (Moringa oleifera). Moringa leaves contain protein, vitamins, minerals, and antioxidants that are beneficial for the growth of broiler chickens, so they have the potential to be an economical feed substitute. This study aims to determine the economic feasibility of a broiler chicken business with moringa leaf flour substitution in feed, through analysis of production costs, revenue, income, R/C ratio, and Break Even Point (BEP). The research was conducted at the Experimental Garden of the Faculty of Agriculture, Abulyatama University, Blang Bintang District, Aceh Besar Regency, for four weeks in February–March 2025. The method used was a Completely Randomized Design (CRD) with four treatments and four replications, namely: P0 (100% commercial feed), P1 (97% commercial feed + 3% moringa leaf flour), P2 (94% commercial feed + 6% moringa leaf flour), and P3 (91% commercial feed + 9% moringa leaf flour). The results showed that production costs between treatments were relatively similar and not statistically significantly different. Descriptively, the highest income, revenue, and R/C ratio values ​​were obtained in treatment P3, while treatment P1 showed the lowest results. The lowest BEP value was also found in treatment P3, which indicates a better level of business efficiency. The results of the analysis of variance showed that the substitution of moringa leaf flour did not have a significant effect on all observed economic parameters (P>0.05). However, the use of moringa leaf flour up to 9% in broiler chicken rations shows more profitable economic potential and can be used as an alternative feed in an effort to increase the efficiency of broiler chicken farming businesses.